Robot-Assisted Therapy for Autism Spectrum Disorders with (Partially) Autonomous Control: Challenges and Outlook - Thill Serge; Pop Cristina A; Belpaeme Tony; Ziemke Tom; Vanderborght Bram (Paladyn, 2012)
Robot-assisted therapy (RAT) is an emerging field that has already seen some success and is likely to develop in the future. One particular application area is within therapies for autism spectrum disorders, in which the viability of the approach has been demonstrated.